Peran Pembimbing Rohani dalam Penguatan Diri pada Pasien Kanker Serviks di RSUD Banyumas - Putri Ledisa Olii; Muridan Muridan (JURNAL ILMIAH NUSANTARA, 2026)
Cervical cancer is a chronic illness that affects not only patients' physical conditions but also their psychological and spiritual well-being. The diagnosis, prolonged treatment, and bodily changes often trigger anxiety, despair, and decreased self-confidence. This condition indicates that cervical cancer management requires more than medical treatment alone; it also needs spiritual support that addresses patients' inner strength. This study aims to analyze the role of spiritual counselors in strengthening self-empowerment among cervical cancer patients at RSUD Banyumas. This research employed a descriptive qualitative method with a case study approach involving a patient identified in the RSUD Banyumas. Data were collected through observation, interviews, and direct spiritual guidance activities. The findings reveal that spiritual guidance plays a significant role in fostering inner peace, enhancing self-acceptance, and strengthening patients' hope and motivation throughout the treatment process. Spiritual reinforcement provided through prayer, encouragement, and emotional support helps patients face their illness with greater patience and optimism.